2000
DOI: 10.1046/j.1525-1373.2000.22518.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death Induction by CTL: Perforin/Granzyme B System Dominantly Acts for Cell Death Induction in Human Hepatocellular Carcinoma Cells

Abstract: Cell death induction by cytotoxic T lymphocytes (CTLs) is an important thesis for the understanding of tumor immunotherapy. In the current study we investigated the molecular machinery of CTL-induced cell death in human hepatocellular carcinoma cell lines (HCC lines). CTLs prepared from human peripheral blood induced cell death in all tested HCC lines. As the CTL-induced death system, the effectiveness of Fas ligand/Fas and/or Perforin/Granzyme B systems has been suggested, whereas cell death induction by CTLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Tested cell lines were expressing Fas and showed the sensitivity to Fas Ab only in the presence of actinomycin D, consistent with our previous report. 31 Fas-mediated cell death in all tested cell lines was completely suppressed by HGF pretreatment. Especially, SK-Hep1 cells highly expressed Fas (same level as Jurkat) and displayed a sensitivity to agonistic Fas Ab in a dose-dependent manner.…”
Section: Cell Survival Initiated By Some Growth Factors Has Been Wellmentioning
confidence: 83%
“…Tested cell lines were expressing Fas and showed the sensitivity to Fas Ab only in the presence of actinomycin D, consistent with our previous report. 31 Fas-mediated cell death in all tested cell lines was completely suppressed by HGF pretreatment. Especially, SK-Hep1 cells highly expressed Fas (same level as Jurkat) and displayed a sensitivity to agonistic Fas Ab in a dose-dependent manner.…”
Section: Cell Survival Initiated By Some Growth Factors Has Been Wellmentioning
confidence: 83%
“…As cytotoxic T lymphocyte (CTL)-induced cell death is initiated by the Perforin/Granzyme B pathway (Hayashida et al., 2000), we detected the mRNA expression of Perforin/Granzyme B in allografts. Logically, the levels of both Perforin and Granzyme B were lower in the grafts from iPS-DCregs-treated recipients compared with the grafts from the non-treatment group.…”
Section: Resultsmentioning
confidence: 99%
“…Tc17 cells, a unique subset of CD8 + T cells, were found in the lung following primary challenge with influenza A and protected against lethal influenza challenge [30, 31]. Cytotoxicity can be induced by two distinct molecular pathways: up-regulation of perforin, or up-regulation of FasL (CD95L) [32, 33]. In our study, we found that high level expressions of IFN- γ and perforin were observed to associate with CD8 + T cells, not the IL-17.…”
Section: Discussionmentioning
confidence: 99%